Dynamic DNA Methylation Changes of Tbx21 and Rorc during Experimental Autoimmune Uveitis in Mice - Yiguo Qiu; Yunyun Zhu; Hongsong Yu; Chunjiang Zhou; Aize Kijlstra; Peizeng Yang (Hindawi Limited, 2018)
The key transcription factors of T helper cell subpopulations, including T-bet, GATA3, RORγt, and Foxp3 are involved in various autoimmune diseases. Whether methylation of these master transcription factors is associated with the development of experimental autoimmune uveitis (EAU) and the possible epigenetic regulatory mechanisms involved has however not yet been addressed. In our study, significant methylation changes in both Tbx21 and Rorc were observed in one CpG site in the retinas of EAU mice. Two CpG sites of Tbx21 and one CpG site of Rorc showed significant dynamic methylation changes in the RPE-choroid complex during EAU. The mRNA expressions of Tbx21 and Rorc in both the retinas and RPE-choroid complexes correlated with the methylation changes at the various time points during EAU development. The methylation changes were associated with the production of the Th1/Th17 cells' signature cytokines, IFN-γ and IL-17. Dynamic changes in mRNA expression of DNA methyltransferases (DNMT1) were also noted, which may be related to the observed methylation changes of these genes. The present study provides evidence that DNA methylation of Tbx21 and Rorc may be associated with the development of EAU. DNMT1 activation may have an important effect on regulating DNA methylation dynamics.